TINJAUAN PENDIDIKAN MENURUT PANDANGAN AL-GHAZALI - Setiawan, Eko (J-PAI: Jurnal Pendidikan Agama Islam, 2015)
al-Ghazali was a great scholar who pays considerable attention to education. Educational practices and the concept of education has been used extensively by the paedagog until today. This type of education that developed seemed to be influenced by views on sufism and jurisprudence. Educational concept put forward a systematic and comprehensive also consistently in line with the attitude and personality as a sufi. Al-Ghazali's concept of education is an application and a response from the answer to the social problems it faces today.Keywords: education, Islam, al-Ghazali